Genetic disorders of collagen. Issue 1 (January 1987) - Tsipouras, P; Ramirez, F
Abstract : Osteogenesis imperfecta, Ehlers-Danlos syndrome, and Marfan syndrome form a group of genetic disorders of connective tissue. These disorders exhibit remarkable clinical heterogeneity which reflects their underlying biochemical and molecular differences. Defects in collagen types I and III have been found in all three syndromes.